Members’ Perception of Service Quality Provision among Agricultural Marketing Cooperative Societies in Rural Kaliua District, Tanzania - Richard Ibrahim Msuya (SAGE Open)
Agricultural Marketing Cooperative Societies (AMCOS) serve both business and association roles. While the association role emphasizes collective action, the business role focuses on generating surplus and maximizing member welfare. To sustain loyalty, AMCOS must ensure service quality. This study examines members’ perceptions of AMCOS service quality in rural Kaliua District, Tanzania, offering a unique perspective beyond financial cooperatives by integrating qualitative and quantitative insights. A cross-sectional survey was conducted with eight randomly selected AMCOS, involving 239 respondents. Primary data were collected through structured questionnaires and Focus Group Discussions (FGDs). The SERVQUAL model was used to assess service quality, with quantitative data analysed using descriptive statistics and paired samples t -tests, while thematic analysis was applied to qualitative data. Findings indicate that AMCOS service quality was unsatisfactory, with reliability as the most problematic dimension. Members’ expectations did not align with their perceptions. Compared to similar studies in Tanzania, service quality challenges were linked to inadequate funds, bureaucratic delays in delivering tobacco inputs, and unskilled board members and management. To improve service quality, AMCOS should allocate sufficient funds for regular governance training to enhance board and management competence. Additionally, the Tanzanian government, through the Ministry of Agriculture and the Registrar of Cooperatives, should revise mechanisms to ensure timely delivery of farm inputs to tobacco farmers.